Kateryna Dysa, Ukrainian Witchcraft Trials: Volhynia, Podolia, and Ruthenia, 17th-18th Centuries (Budapest-New York: CEU Press, 2020), 254 pages - BUZĂ, Alexandra-Maria (Studia Universitatis Babeș-Bolyai Historia, 2025)
Witchcraft trials in Eastern Europe have not received the same attention as those in the West, a fact attributed in part to the limited documentary evidence, and to their less spectacular nature. In Ukraine, cases were handled in a remarkably rational manner for that era, lacking the intensity encountered in Western Europe. This approach was due, on the one hand, to the enforcement of the Magdeburg Law by the city councils, and, on the other hand, to the influence of the Orthodox Church on the studied area, determining the non-application of Western demonological principles. The accusations appeared mainly in the context of social conflicts or serious events, such as the death of a child or the loss of crops, and could be brought against anyone, without there being a fixed image of the witch or a major concern for a pact with the Devil.